Pengaruh Relaksasi Terhadap Nyeri Dan Kemajuan Persalinan Pada Ibu Bersalin - Suprapti Suprapti (IJMT : Indonesian Journal of Midwifery Today, 2021)
Relaxation is a non-pharmacological pain control method which is widely used in the UK. Steer explains that as many as 34 percent of patients use this relaxation method. This pain control technique, including relaxation techniques, teaches the patient to always minimize the activity of the sympathetic and autonomic nervous systems. Relaxation can also be said as a process of making the body and mind rest from all kinds of physical burdens as well as psychological burdens, making the patient calmer. This relaxation technique can make the blood circulation in the uterus, placenta, and fetus smooth so that the need for oxygen and food in the fetus is met. Good blood circulation will cause the muscles that are directly related to the womb as well as the fetus such as the pelvic, abdominal and back muscles to become loose and weak. While at the time of labor, relaxation makes the contraction process will take place naturally, safely, and smoothly. In addition to relaxing the patient, knowledge of how to breathe properly can also help overcome some of the difficulties commonly experienced by pregnant patients. The design of this study used a prospective cohort descriptive design. The population in this study were pregnant women during childbirth at BPM Suprapti, S. ST, M Case. Replacing Gresik as many as 20 people. The procedure of this study was carried out by implementing the application of intranatal relaxation to pregnant women during labor whose clients had previously received an explanation of the research and had signed a letter of approval. relaxation therapy. Of the 10 people who received relaxation therapy, it was known that 10 gave birth normally with the duration of labor from the first stage of the active phase until the baby was born for 3 hours. While 10 respondents who did not receive relaxation therapy, it was found that 5 people experienced normal labor with the length of the labor process starting from the first stage until the baby was born for 6 hours, 2 people were referred because of the prolonged active phase while 3 people were not yet inpartu.